Seneca and Synaesthesia. The sensory aspect of the tragedies - Pypłacz, Joanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The present article discusses selected examples of the poetic means which Seneca uses in order to achieve the effect of synaesthesia in his tragedies. An analysis of these examples reveals that the poet makes the most of the Latin language’s semantic and musical potential and in doing so achieves quite spectacular sensory effects.